Efficient one-pot synthesis of alpha-amino phosphonates catalyzed by bismuth nitrate pentahydrate - Bhattacharya, Asish K.; Kaur, Tanpreet (Synlett, 2007)
A simple, efficient, and environmentally benign method has been developed for the synthesis of alpha-amino phosphonates through a one-pot reaction of aldehydes with amines and diethyl phosphite in the presence of bismuth nitrate pentahydrate as a catalyst. Some of the major advantages of this protocol are: good yields, the involvement of a less-expensive and non-toxic catalyst, mild and solvent-free reaction conditions and also tolerance towards other functional groups present in the substrates. Eighteen examples are described, highlighting the substrate scope of the reaction.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; bismuth nitrate pentahydrate; synthetic methods

Amberlite-IR 120 catalyzed three-component synthesis of alpha-amino phosphonates in one-pot - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Tetrahedron Letters, 2008)
A simple, efficient, and environmentally benign method for a three-component reaction of an amine, an aldehyde or a ketone, and diethyl phosphite catalyzed by Amberlite-IR 120 resin has been developed to afford alpha-amino phosphonates in high yields and short reaction times under solvent-free reaction conditions. The major advantages of the present method are good yields, inexpensive, ecofriendly and reusable catalyst, mild and solvent-free reaction conditions and tolerance towards various functionalities present in the substrates. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; ion-exchange resin; multi-component reaction

Synthesis of alpha-amino phosphonates by three component condensation of carbonyl compound, amine, and dialkyl phosphite using Yttria-zirconia based Lewis acid catalyst - Ramalingam, S.; Kumar, Pradeep (Catalysis Letters, 2008)
An efficient Yttria-zirconia Lewis acid catalyzed one-pot synthesis of alpha-amino phosphonates by three component coupling reaction of a carbonyl compound amine and dialkyl phosphates is described in good to high yield.
Keywords: alpha-amino phosphonates; three component coupling; Yttria-zirconia based Lewis acid catalyst